2012
DOI: 10.1158/1055-9965.epi-12-1036
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Genes Related to Obesity, Weight, and Weight Change and Risk of Contralateral Breast Cancer in the WECARE Study Population

Abstract: Background Body mass index (BMI), a known breast cancer risk factor, could influence breast risk through mechanistic pathways related to sex hormones, insulin resistance, chronic inflammation and altered levels of adipose derived hormones. Results from studies of the relationship between BMI and second primary breast cancer have been mixed. To explore the relationship between BMI and asynchronous contralateral breast cancer (CBC), we examined whether variants in genes related to obesity, weight and weight chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Leptin can activate POMC and inhibit NPY [38] and is involved in inflammatory response and regulation of insulin sensitivity. While we did not observe associations between LEP SNPs and breast cancer risk, similar to reports by others [8,10,39], we did observe several associations between LEPR and breast cancer risk. The biological effects of LEP are exerted through binding to the leptin receptor.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Leptin can activate POMC and inhibit NPY [38] and is involved in inflammatory response and regulation of insulin sensitivity. While we did not observe associations between LEP SNPs and breast cancer risk, similar to reports by others [8,10,39], we did observe several associations between LEPR and breast cancer risk. The biological effects of LEP are exerted through binding to the leptin receptor.…”
Section: Discussionsupporting
confidence: 91%
“…Both adiponectin and leptin are adipokines that are secreted by adipocytes [7]. Leptin has been directly associated with obesity, while adiponectin has been inversely associated with obesity and visceral fat accumulation [8]. Among these genes, LEP and LEPR have been studied the most with breast cancer and have been associated with obesity [9].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that Kaklamani et al [39] reported a significant association between FTO rs1477196 and breast cancer risk in predominantly Caucasian patients, Kusinska et al [40] found no such relation with the FTO variants rs993909 and rs9930506 in a sample of 134 Polish women. The same negative result was obtained by Brooks et al when they tried to find a relationship between FTO variants associated with BMI and the subsequent risk of second primary breast cancer [41]. This is probably because the mechanisms for the development of metastasis do not involve the same risk factors as first tumor emergence.…”
Section: Fto Polymorphisms and Cancermentioning
confidence: 51%
“…Previous studies have suggested that cancer risk factors include an unhealthy life style, environmental pollution, radiation, infection, and immunity dysfunction 45 46 47 . Additionally, studies have increasingly focused on genetic factors 48 49 50 . In recent years, numerous studies reported an association between the SDF-1 rs1801157 polymorphism and cancer susceptibility, but the results were inconsistent or inconclusive.…”
Section: Discussionmentioning
confidence: 99%